Hello, my name is Doris [videorecording (DVD)] - Field, Sally; Greenfield, Max, 1980-; Daly, Tyne (Columbia Tristar Home Entertainment, 2016)
When Doris Miller meets John Fremont sparks fly-at least for Doris. In the cluttered house she shared with her late mother. When Doris begins showing up at John's regular haunts, she wins over his Williamsburg friends. Her new life brings Doris a thrilling perspective, but also creates a rift between her and her longtime friends and family, who believe she's making a fool of herself over a guy half her age.